ELT Novice Teachers’ Competence for Teaching Speaking Class - Hasanah, Nur Izatil; Angrum, Alna Triskaya (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2020)
This study conducted to describe the competence of novice teacher in speaking class. The method of this research is qualitative methods. The sample of this research used two novice teachers. In collecting data, the researcher uses observation and interview. The researcher did observation with several techniques, the first is joining the class then giving a checklist on the observation paper based on the situation in the class. The researcher recorded the interview data. The result of this research shows that the competence of novice teacher is good, because she has four teacher competence. The first competence is pedagogic competence because the novice teacher has ability to manage the teaching and learning process. She can make the student to understand what she said in front of the class. The novice teacher can take the action to improve the quality of reflective learning. The second competence is personality competence, she has a wise and stable personality. She has a good personality as a teacher, as measured by indicators show independence in acting as educators and have a work ethic as an educator. The third competence is professional competence, she has the ability of professionals to be possessed teacher in the learning process, because she can be controlling the material, managing learning programs, managing the classroom, using a media source, mastering the foundations of education, and managing the interaction of learning teaching. The last competence is social competence and she is good in this competence too, because she has the ability to communicate, get along in school and society.